Gender transformative intervention profile 5: Addressing normative constraints to building women’s economic resilience in the cassava agrifood system in Nigeria - Adeyeye, Olajumoke; Adedeji, Anthony; Oluwadepo, Jumoke; Adesiji, Taiwo; Ogundiran, Tomi (CGIAR Initiative on Gender Equality, 2024)
Women account for a significant portion of the agricultural labor force, representing 43% of the total workforce in agriculture across low- and middle-income countries (Singh et al., 2022).1 Yet despite their substantial involvement, women often face unequal norms that hinder their ability to participate fully and benefit meaningfully from agricultural activities. Social norms are the informal rules that prescribe behavior considered to be acceptable, appropriate, and obligatory within a group (Cislaghi & Heise, 2018).2 Gender norms, in particular, define acceptable and appropriate behavior for women and men (Cislaghi & Heise, 2020)3 and can create gender inequalities in agricultural development outcomes. These norms can significantly shape women’s access to resources and training and their decision-making power, ultimately affecting their productivity and economic opportunities.